(3CfS GdSejQ aj fhGOQ GdaQROb hLQjQs - (3Ydj Hf CMeO Hf bGSe Hf ehSi Hf eUHGM GdRQhjdj , (B1136 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi edcfG CYfI GdHdGZI hGdHjGf CeG HYO aEf GdYde CfaS Jfab ajg cQGFe GdfahS s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg (B: (3bGd GHf QTjb(B: (3hGdGaJNGQ ghG GdeOM HYjfg EdG Cf GdTGYQ jNU Hg faS hbheg g` (B[ (3GfJgi (B] (3bGd OYHd (B: (3CaNQ HjJ bGdJg GdYQH bhd cYH Hf eGdc s
(3GdfSNI HgG MhGTs
(3HCKfGFgG HjGVs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdCOHs